PERAN PEMERINTAH DALAM PENGEMBANGAN OBJEK WISATA AIR TERJUN SUNGAI MURAI DI KELURAHAN ROKAN, KECAMATAN ROKAN IV KOTO, ROKAN HULU - Sofyan Hadi; Adip Nas Ijlal; A. Farhan; Annisa Zaari Amni; Atikah Nandini; Humay Arsyakinah Tanjung; Pikri Wahyudi; Putri Oktaviani; Rema Sepmawati; Rizki Lestari; Selvi Pebriani (Universitas Methodist Indonesia, 2022)
The purpose of this journal is to provide broader knowledge related to efforts to preserve and develop local tourism objects, namely Sungai Murai Waterfall so that tourists and the surrounding community can enjoy it as a natural recreation area. The government of Rokan Hulu Regency explores all the potentials it has and requires local governments to administer governance and develop regional potential. The first step that can be taken by local governments is to see the potentials they have and be able to manage them well and fight for them. The activity carried out by the UNRI 2022 Kukerta students in the form of installing a signboard